PRODUKSI SELULASE OLEH KAPANG Aspergillus sp. HASIL ISOLASI DARI LIMBAH PENGOLAHAN SAGU (Metroxylon sp.) DENGAN VARIASI KONSENTRASI INOKULUM PADA FERMENTASI TERENDAM STATIS - Anisa Rachma Sari; Endang Kusdiyantini; MG Isworo Rukmi (Jurnal Akademika Biologi, 2017)
Sago processing waste is one of agro-industry waste, which contains cellulose 19,55% and lignin 25%. Genus Aspergillus has been widely known as cellulase-producing fungi. Isolation of Aspergillus from sago processing waste is expected to get a potential isolates indegenous cellulolytic fungi. Cellulase (EC 3.2.1.4) is an enzyme that can break down cellulose into glucose monomer form, with consists of three components that work in synergy are endoglucanase, eksoglucanase and β-glucoside. This study aims to obtain isolates of Aspergillus sp. cellulolitic potential from sago processing waste and cellulase production of the cellulolytic isolates in various concentrations of inoculum. The study was conducted using completely randomized design (CRD) 1 factor of 4 levels of inoculum concentration treatments were 0%, 2,5%; 5%; and 10% with three replications. The observed variables are biomass, CMCase activity and FPase activity. Data were analyzed by ANOVA with a significance level 95%. The result of isolation, two isolates of Aspergillus namely A. flavus and A. paradoxus with cellulolitic index respectively 2,63 and 2,06. Cellulase activity isolate of A. flavus either endoglucanase (CMCase) or total cellulase (FPase) are not affected by the concentration of inoculum.Keywords: cellulase, sago waste, Aspergillus, inoculum